The Effectiveness of A Training Program Using Vertical Jump Device (Vertimax) on Some Biomechanical Variables in Performance of Undulating Serve Skill in Volleyball for Players - Aqeel Yousif Naser (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Development of  biomechanical elements associated with  performance and precision of some fundamental volleyball skills is where  research is most important using exercises on  training device (vertimax), which considers  demands of  particular talent when training on it, as training is carried out according to  motor paths of each skill independently to advance  physical elements of  trained skills, which are reflected in  biomechanical aspects of each skill, which differs from  traditional methods of giving physical exercises, as  physical and skill training on this device is closer to  nature of  players' talent performance on  field. In addition,  exercises have been built on a mechanical basis that matches  character of  skill's real on-field performance.   research's objectives are to design exercises with  Verti Max device that are appropriate for  research sample's abilities and to determine how these exercises affect  development of certain biomechanical markers of young volleyball players' proficiency with  undulating serve from  jump.  research community consists of young volleyball players from Babylon clubs (Al-Mahaweel Club) youth category, numbering (16) players.  following criteria were used to choose  research sample:  They will be  Al-Mahaweel Sports Club's young players for  2022–2023 season, and there will be ten of them.   players were split up into two groups by  researcher: a control group and an experimental group, which was assigned a number of five, numbering (5), and they constitute (63%) of  total community. This was done by drawing lots, as  investigator came to  conclusion that  suggested workouts have an effect in developing  skill of crushing in some biomechanical variables (angular velocity of  striking arm, shoulder angle now of striking, instantaneous velocity of  ball’s exit, and torso angle at  moment of striking).